The Protein Composition of Bovine Milk from Once-a-Day and Twice-a-Day Milking Production Systems in New Zealand - van der Zeijden M; Ellis A; Lopez-Villalobos N; Li S; Roy NC; McNabb W (MDPI (Basel, Switzerland), 2023)
An increasing number of dairy farmers in New Zealand (NZ) have adopted a once-a-day (OAD) milking production system, and little is known about the impact of this production system on milk protein composition. The objective of this study was to evaluate the effect of OAD milking on the protein composition in milk from individual cows. Milk was sampled in early, mid-, and late lactation from cows kept at Massey University farms Dairy No. 1 (OAD milking) and Dairy No. 4 (TAD milking) in Palmerston North, NZ. The yields of total milk and milk solids, the proximate composition, and the protein composition were determined. Results showed that OAD milking yielded less milk and milk solids than TAD milking. However, no significant differences in protein, fat, and lactose contents were found. While the proportions of total casein (CN), total whey proteins, αs1-CN, β-CN, and β-lactoglobulin were not affected by the milking frequency, milk from a OAD milking system contained higher proportions of αs2-CN and κ-CN and lower proportions of α-lactalbumin. These proteins also changed differently throughout the milking season in a OAD milking system than in a TAD milking system. These changes in the protein composition of the milk observed in a OAD milking system could have implications for its processing properties and product quality.
Keywords: milking frequency; once-a-day milking; seasonal variation; protein composition